Changes in pharmaceutical retail market and regional inequality of community pharmacists accessibility in mainland China: a retrospective cross-sectional study. Issue 11 (21st November 2022) - Feng, Zhen; Ye, Yun; Ye, Hua; Tang, Zhijia
Abstract : Objectives: To describe the development of pharmaceutical retail market and community pharmacists in mainland China and identify challenges from both government and business perspectives. Design: A retrospective cross-sectional study. Setting: Community pharmacies providing primary care in mainland China. Participants: Community pharmacies and community pharmacists in all 31 provincial units in mainland China registered in the National Medical Products Administration during 2014–2020. Number of community pharmacies ranged from 433 529 (2014) to 553 892 (2020). Number of community pharmacists ranged from 129 895 (2014) to 541 264 (2020). Primary and secondary outcome measures: Changes in pharmaceutical retail market and accessibility of community pharmacists over the study period. We also examined the qualification of pharmacists and regional differences. Results: During 2014–2020, the total number of retail companies and pharmacies increased by 47.6% and 27.4%, respectively. The national retail chain rate boosted from 39.4% to 56.5%, and average number of stores per company increased from 40.2 to 49.7. The number of community pharmacists rose by 316.7%. Regarding accessibility, number of pharmacy stores per 10 000 inhabitants increased from 3.2 to 3.9; the average number of pharmacists per store and per 10 000 residents rose from 0.30 to 0.98 and from 0.95 to 3.83. However, the proportion holding a postgraduate or bachelor's degree dropped to one-third. Pharmacy resources were unevenly distributed across the country. Correlations were observed between economic indicators and number of pharmacy stores and pharmacists (p<0.05). Conclusions: In general, the accessibility and centralisation of retail pharmacies in China have shown a steady growth with a sign of regional disparities. The availability of community pharmacists has increased significantly, although with an unreasonable composition of academic qualifications and a shortage of personnel. Further efforts are necessary to provide sufficient pharmacy resources for community settings and resolve regional disparities.